Advances in the treatment of intraocular malignancies: A literature review - Cui, Yanyan; Yin, Shan; Qin, Xuejiao; Jiao, Wanzhen; Ren, Anqi; Wang, Fei; Zhao, Bojun (Frontiers in Medicine, 2022)
Intraocular malignant tumors including primary and metastatic tumors, are mainly found in Retina and uvea, and very few cases originate from the sclera and optic nerve. Intraocular tumors can endanger the patient’s vision and even life, and proper treatment is vital. There have been several traditional treatments for intraocular tumors, such as radiotherapy, chemotherapy and surgery. In recent years, new methods have been developed in clinical applications including anti- vascular endothelial growth factor (VEGF )and gene therapy. This paper aims to provide a timely review about recent progress in the treatment of intraocular malignant tumor.